2015
DOI: 10.1371/journal.pone.0139200
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Assessment of Outer Membrane Vesicle Production in Escherichia coli

Abstract: The production of outer membrane vesicles by Gram-negative bacteria has been well documented; however, the mechanism behind the biogenesis of these vesicles remains unclear. Here a high-throughput experimental method and systems-scale analysis was conducted to determine vesiculation values for the whole genome knockout library of Escherichia coli mutant strains (Keio collection). The resultant dataset quantitatively recapitulates previously observed phenotypes and implicates nearly 150 new genes in the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 67 publications
6
77
0
1
Order By: Relevance
“…As other bacteria also secrete EVs, including E. coli , 44, 45 we were curious if they likewise possess similar surface modulatory or inhibitory activities. Using the same concentration (12.5 μg/ml) of pEVs from two additional strains, namely S. epidermidis and E. coli , we tested their ability to bind to polystyrene and inhibit A. baumannii biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
“…As other bacteria also secrete EVs, including E. coli , 44, 45 we were curious if they likewise possess similar surface modulatory or inhibitory activities. Using the same concentration (12.5 μg/ml) of pEVs from two additional strains, namely S. epidermidis and E. coli , we tested their ability to bind to polystyrene and inhibit A. baumannii biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
“…coli is important for the maintenance of outer membrane integrity. It has been described that mutations in any of the tol-pal genes confer a defect in the outer membrane that leads to increased MV production [19–21]. …”
Section: Resultsmentioning
confidence: 99%
“…A recent study analyzing MV production by the mutant strains of the Keio Collection identified around 150 genes involved in the vesiculation process. It was shown that mutations altering outer membrane structures generally lead to hypervesiculation phenotypes [21]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, disruption of crosslinks between the outer membrane and peptidoglycan layer promote MV release (Deatherage et al, 2009; Schwechheimer et al, 2014, 2015). Recently, a high-throughput screen of a whole genome E. coli knockout library identified 171 genes that affect vesicle biogenesis (Kulp et al, 2015). Interestingly, mutants of oxidative stress response pathways correlated with a hypovesiculation phenotype.…”
Section: The Basics: Biogenesis and Functions Of Bacterial Membrane Vmentioning
confidence: 99%